Animal Locomotion 2010
DOI: 10.1007/978-3-642-11633-9_22
|View full text |Cite
|
Sign up to set email alerts
|

Wake patterns of the wings and tail of hovering hummingbirds

Abstract: The flow fields of slowly flying bats and fasterflying birds differ in that bats produce two vortex loops during each stroke, one per wing, and birds produce a single vortex loop per stroke. In addition, the circulation at stroke transition approaches zero in bats but remains strong in birds. It is unknown if these difference derive from fundamental differences in wing morphology or are a consequence of flight speed. Here, we present an analysis of the horizontal flow field underneath hovering Anna's hummingbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 17 publications
2
20
0
Order By: Relevance
“…These new but still simplified models are based upon previous hypotheses of the single (Rayner 1979) and bilateral (Altshuler et al 2009) vortex loops and other possible explanations for the flow patterns observed here (Fig. 5).…”
Section: Wake Patternmentioning
confidence: 85%
See 3 more Smart Citations
“…These new but still simplified models are based upon previous hypotheses of the single (Rayner 1979) and bilateral (Altshuler et al 2009) vortex loops and other possible explanations for the flow patterns observed here (Fig. 5).…”
Section: Wake Patternmentioning
confidence: 85%
“…It had been proposed that a hovering hummingbird generates one vortex ring per stroke (Rayner 1979;Ellington 1984;Pennycuick 1988;Rayner and Gordon 1998), which would match the vortex shedding pattern proposed for larger birds during slow flight (Spedding et al 1984(Spedding et al , 2003. Altshuler et al (2009) made PIV measurements in a horizontal plane beneath the hummingbirds close to the tail. These measurements revealed source flows induced by vortices, which appeared on each side of the animal at an interval of double the wingbeat frequency.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…It is well known that aircraft in ground effect experience pitch instability, which is usually corrected by a highly elevated tail plane in order to shift the centre of pitch downstream while maintaining the aerodynamic centre of height upstream (for details, see [33]). Altshuler et al [34] proposed that hummingbirds use their tails to deflect the flow created by the wings in order to maintain pitch stability Figure 6. Comparison of average weight-normalized mechanical power estimates for Anna's hummingbirds with theoretical estimates derived from two helicopter models for hovering in ground effect (IGE) and out of ground effect (OGE) ( [28,29]; as cited in [1,2]), with vertical thrust assumed to be constant.…”
Section: Discussionmentioning
confidence: 99%